Intraoperative Radiotherapy in Newly Diagnosed Glioblastoma (INTRAGO): An Open-Label, Dose-Escalation Phase I/II Trial. Issue 1 (8th March 2018) - Giordano, Frank A; Brehmer, Stefanie; Mürle, Bettina; Welzel, Grit; Sperk, Elena; Keller, Anke; Abo-Madyan, Yasser; Scherzinger, Elisabeth; Clausen, Sven; Schneider, Frank; Herskind, Carsten; Glas, Martin; et al.
Abstract: BACKGROUND: The median time to recurrence of glioblastoma (GB) following multimodal treatment is ∼7 mo. Nearly all cancers recur locally, suggesting that augmenting local treatments may improve outcomes. OBJECTIVE: To investigate whether intraoperative radiotherapy (IORT) to the resection cavity is safe and effective. METHODS: INTRAGO was a phase I/II trial to evaluate the safety and tolerability of IORT with 20 to 40 Gy of low-energy photons in addition to standard radiochemotherapy (ClinicalTrials.gov ID, NCT02685605). The primary endpoint was safety as per occurrence of dose-limiting toxicities. Secondary endpoints were progression-free survival (PFS) and overall survival (OS). We also performed an exploratory analysis of the local PFS (L-PFS), defined as recurrence within 1 cm of the treated margin. RESULTS: Fifteen patients were treated at 3 dose levels. Of these, 13 underwent incomplete resection, 6 had unresected satellites, and 3 did not receive per-protocol treatment (PPT). The MGMT promoter was unmethylated in 10 patients. The median follow-up was 13.8 mo. The majority of grade 3 to 5 adverse events were deemed unrelated to IORT. Five cases of radionecrosis were observed, 2 were classified as grade 3 events. Other grade 3 events judged related to radiotherapy (external-beam radiotherapy and/or IORT) were wound dehiscence (n = 1), CSF leakage (n = 1), cyst formation (n = 1). No IORT-related deaths occurred. The median PFS was 11.2 mo (95% confidence interval [CI]: 5.4-17.0) for all patients and 11.3 mo (95% CI: 10.9-11.6) for those receiving PPT. The median L-PFS was 14.3 mo (95% CI: 8.4-20.2) for all patients and 17.8 mo (95% CI: 9.7-25.9) for those receiving PPT. The median OS was 16.2 mo (95% CI: 11.1-21.4) for all patients and 17.8 mo (95% CI: 13.9-21.7) for those receiving PPT. CONCLUSION: These data suggest that IORT is associated with manageable toxicity. Considering the limitations of a 15-patient phase I/II trial, further studies aimed at assessing an outcome benefit are warranted.